Financing needs of nascent entrepreneurs in Chile: does gender matter? - Gianni Romani; Miguel Atienza; Ernesto Amorós (European Regional Science Association (ERSA), 2010)
Funding is critical during new firms' creation and the most sources of funding in the early stages of entrepreneurial ventures are informal investors (Family, Friends, the Founding entrepreneurs themselves, and the foolhardy strangers, also known as business angels). Entrepreneurs in the initial stages are the main users of informal financing, more specifically those denominated according to the GEM definition as nascent entrepreneurs; that is, those who are involved in establishing a business or those who have made the leap from the conception of the business to its actual gestation (Reynolds et al., 2005). Informal investment has come to the attention of researchers, mostly in the United States and Europe, and very scarcely in Latin America. Nevertheless, in recent years there has been a call to study entrepreneurship taking in consideration the perspective of gender (Brush, 1992; Bird and Brush, 2002). In Chile, studies of this nature are scarce. For this reason in order to find out more of how the nascent entrepreneurs fund theirs ventures, the main objective of this article is to explore the gender differences that could exist in the financing needs of nascent Chilean entrepreneurs with regard to: Amount needed to start the business; outside financing expectations, employment creations expectations, socio-demographic characteristics, perception related to entrepreneurship. The analysis is based on a representative sample of the Chilean adult population between 18 and 64 years of age, using data from the GEM from the years 2007 and 2008. Since this is an exploratory study, we propose separating the nascent entrepreneurs by gender and using descriptive statistics and Mann - Whitney U test (non-parametric test for two independent samples). The results show that there are significant gender differences among nascent entrepreneurs with respect to the amount needed to start a business, socio-demographic characteristics, and in some aspects related to entrepreneurship. These results provide a better understanding of the financial needs of nascent entrepreneurs and the existent differences between women and men. These results can contribute to a better design of public policies to support new venture creations taking into account a gender perspective.
Keywords: 330